206k views
3 votes
(x - y + z) : (y - z + 2w) : (2x + z - 10) = 2:3:5 Then ( 3x + 3z - 2w) : w = ?pgvzcmckyc?​

User Thilanka
by
6.0k points

2 Answers

4 votes

Answer:

19

Explanation:

in question given ,x = 2, y = 3, z = 5 in this way

(3x+3z+2w) and find the value of w . according to given values and put

User Vijay S
by
5.1k points
2 votes

Answer:

4 +30/w . . . . for any w≠0

Explanation:

The given constraints resolve to 2 equations in 4 unknowns. There are an infinite number of solutions.

The ratio requirement means ...

(x -y +z)/2 = (y -z +2w)/3 = (2x +z -10)/5

Considering the first equality, we can multiply by 6 and subtract the right side.

3(x -y +z) -2(y -z +2w) = 0 ⇒ 3x -5y +5z -4w = 0

Considering the first and last expressions, we can multiply by 10 and subtract the right side.

5(x -y +z) -2(2x +z -10) = 0 ⇒ x -5y +3z = -20

These two equations have solutions ...

x = 10 -z +2w

y = 6 + 0.4z +0.4w

Using these expressions in the ratio of interest, we have ...

(3x +3z -2w) : w = (3(10 -z +2w) +3z -2w) : w = (30 -3z +6w +3z -2w) : w

= (30 +4w) : w

Expressed as a mixed number, the ratio of interest is ...

(30 +4w)/w = 4 +30/w . . . . an infinite number of solutions

__

For positive values of w that are divisors of 30, there are 8 possible values:

(w, ratio) = (1, 34), (2, 19), (3, 14), (5, 10), (6, 9), (10, 7), (15, 6), (30, 5)

_____

Check

It might be interesting to substitute the expressions for x and y into our original equation(s).

(x -y +z)/2 = ((10 -z +2w) -(6 +0.4z +0.4w) +z)/2 = (2 -0.2z +0.8w)

(y -z +2w)/3 = ((6 +0.4z +0.4w) -z +2w)/3 = (2 -0.2z +0.8w)

(2x +z -10)/5 = (2(10 -z +2w) +z -10)/5 = (2 -0.2z +0.8w)

All of these expressions are identical, as they should be.

User Ellingsworth
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.